{ 2 3 x + 4 − 3 y + 1 = 1 1 9 2 x − 1 + 3 y = 4
Solve the system of equations above. Submit your answer as the value of x .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Given that { 2 3 x + 4 − 3 y + 1 = 1 1 9 2 x − 1 + 3 y = 4 . . . ( 1 ) . . . ( 2 )
⟹ 3 × ( 2 ) : 3 ( 2 x − 1 ) + 3 y + 1 = 1 2 . . . ( 2 a ) and
( 1 ) + ( 2 a ) : 2 3 x + 4 + 3 ( 2 x − 1 ) 2 3 x + 4 + ( 2 2 − 1 ) 2 x − 1 2 3 x + 4 + 2 x + 1 − 2 x − 1 = 1 1 9 + 1 2 = 1 3 1 = 1 3 1
Note that the right-hand side 1 3 1 is odd, therefore the left-hand side must also be odd. The only way to make the LHS to be odd is 2 x − 1 = 2 0 = 1 , ⟹ x = 1 . Then we note that the L H S = 2 7 + 2 2 − 2 0 = 1 2 8 + 4 − 1 = 1 3 1 = R H S . Therefore x = 1 .
Problem Loading...
Note Loading...
Set Loading...
{ 2 3 x + 4 − 3 y + 1 = 1 1 9 2 x − 1 + 3 y = 4 2 3 x + 4 − 3 ( 3 y ) = 1 1 9 2 3 x + 4 − 3 ( 4 − 2 x − 1 ) = 1 1 9 2 3 x + 4 − 1 2 + 3 ( 2 x − 1 ) = 1 1 9 1 6 ( 2 x ) 3 + 1 . 5 ( 2 x ) = 1 3 1 3 2 ( 2 x ) 3 + 3 ( 2 x ) = 2 6 2 2 x = 2 x = 1